The Potency of Nanosilica Particle Usage From Rice Ash Husk for Material Addition for Making Concrete (Mini Review) - Aditya Wahyu Nugraha (Agroindustrial Technology Journal, 2021)
In the current era, the increase in infrastructure development correlate with the increased use of concrete. This is because currently, many buildings used concrete. However, concrete is prone to damage due to incomplete processes, for example cracking. Based on several studies that have been reviewed, these problems can be minimized by using silica, both micro, and nano sizes. In general, the silica used comes from quartz sand in the concrete mixture that has been studied. On the one hand, the use of silica is beneficial in the manufacture of concrete, but on the other hand it has a negative impact on the environment. If this is not done prevention, the environment will be more damaged. Therefore, this article looks at the potential of silica from rice husk ash and looksÂ Â Â atÂ Â Â theÂ Â Â characteristicsÂ Â Â ofÂ Â Â concreteÂ Â Â withÂ Â Â Â silicaÂ Â Â Â additionÂ Â Â Â fromÂ Â Â Â quartzÂ Â Â Â sand.